Analisis Proses Pembentukan Identitas Remaja dalam Keluarga Broken Home di SMA Panca Budi Medan - Sitompul, Lukmanul Hakim; Tumiran (Islam & Contemporary Issues, 2026)
Adolescence is a crucial developmental stage characterized by the process of identity formation. However, adolescents from broken home families often face psychosocial challenges that may hinder this process. Despite growing concerns about family disruption, limited studies have specifically examined how adolescents construct their identity within the local school context in Medan. This study aims to analyze the dynamics of identity formation among adolescents from broken home families at SMA Panca Budi Medan by exploring internal and external influencing factors, the impacts experienced, and the role of the school in supporting their development. This research employed a qualitative descriptive approach involving 10 informants, consisting of students from broken home families, teachers, and school counselors who directly interact with the students in the school environment. Data were collected through in-depth interviews, participatory observation, and document analysis. The data were analyzed using the Miles and Huberman interactive analysis model, which includes data reduction, data display, and conclusion drawing to identify patterns related to identity formation dynamics among the participants. The findings indicate that adolescents from broken home backgrounds experience several psychological challenges, including insecurity, low self-esteem, confusion in determining life goals, and emotional instability. Internal factors such as personality traits, self-esteem, and coping strategies influence their adaptability, while external factors such as teacher attention, peer support, and participation in extracurricular activities contribute significantly to positive identity development. The study highlights that the school plays a strategic role through counseling services, teacher mentoring, and self-development programs. This research contributes to strengthening the understanding of schools as protective factors in supporting adolescent identity formation within the local context of Medan, particularly for students from broken home families.